Management of coffee leaf miner: Spray volume, efficacy of cartap hydrochloride and impact on parasitism - Melo, Thiago Lima; Raetano, Carlos Gilberto [UNESP]; Nery, Moizés Silva; Cardoso, Adriana Dias; Moreira, Aldenise Alves; Leite, Suzany Aguiar; de Jesus, Thamires Francisca; Silva, Wesley Gil Oliveira; Castellani, Maria Aparecida (Coffee Science, 2019)
The leaf miner is a key pest of coffee and the use of insecticides for its control results in high water consumption. The objective in this study was to evaluate the quali-quantitative aspects of reduced spray volumes with and without the addition of adjuvant, the efficacy of the insecticide cartap hydrochloride in the control of the pest and its effects on the parasitism. Two experiments were carried out in coffee plantations in São Desiderio, BA. Initially, solution of Brilliant Blue tracer (0.15% p v-1) of the 43, 112, 146 and 309 L ha-1 volumes was sprayed with and without the soybean oil methyl ester adjuvant (0.25 % v v-1). Before spraying, water-sensitive cards were fixed to the plants and subsequently used for analyze the droplet spectrum in Gotas 1.0 software. The tracer deposit was determined by spectrophotometry. Posteriorly, the insecticide cartap hydrochloride (0.5 kg a.i. ha-1) was applied in the same volumes and types of spray used in the first test. Infestation rates of pest and parasitism were evaluated before and after application of the insecticide. The quali-quantitative aspects of the sprays were affected by the volume of spray applied, by the adjuvant and by the interaction of the factors. The intermediate volumes yielded better spraying quality without the presence of the adjuvante, with higher number and desity of drops. The spraying volume affected the depoisto the Brilliant Blue tracer in a linear and positive form. The efficacy of the insecticide was prolonged with the lowest volume spray and with adjuvant and its impact on parasitism varied with the volume applied and time after application.
Manejocloridratodo bicho-mineiro:De cartapevolumee impactode pulverização,no parasitismoeficácia do
Keywords: Adjuvant; Application technology; Coffea arabica; Leucoptera coffeella; Spraying tracer